Desarrollar la motricidad gruesa en niños de 10 años de la Escuela Fútbol Club Zapotal - Yance Franco, Eduardo Josué (2023)
The present case study was conducted with a sample of 30 children who are 10 years old, belonging to the Zapotal Soccer Club school, to whom a survey was applied to identify possible gross motor problems, the results show that 46.67% of the children perform sports activities once or twice a week while 30% do it daily, 60% of the children feel very confident when performing activities that require coordination, However, 10% feel not very confident and another 3.33%, 6.67% respond that it is often difficult to change direction quickly while playing soccer or performing other physical activities and 76.67% have no difficulties, 16.67% say that it is difficult to run quickly, 6.67% jump on one foot, 20% say that it is difficult to throw or kick a ball accurately and 56.67% say they have no difficulties at all. Regarding parents or guardians, 63.33% say they are very satisfied, 6.67% are not very satisfied, 70% say that coordination, balance or agility have improved notably, while 10% say they have not noticed any changes, 16.67% say that some of the activities and training offered at the school are adequate and 3.33% say they are not, and 76.67% of the parents consider that the school should implement more activities or programs to improve their child's coordination, balance or agility, while 10% say they have not noticed any changes, and 76.67% of the parents consider that the school should implement more activities or programs to improve their child's coordination, balance or agility.